Arquitectura de la información en portales de noticias: Implicaciones relacionadas con sobrecarga cognitiva y desorientación del usuario - de Oliveira, Henry Poncio Cruz [UNESP]; Lazzarin, Fabiana Aparecida [UNESP] (My University, 2015)
Discusses problems related to cognitive overload and user disorientation in digital information environments, specifically on news portals of Ceará‘s Cariri. Arises from research restlessness explained as follows: can Information Architecture elements be mechanisms to prevent cognitive overload and user disorientation? It analyzed whether Digital Information Architecture elements can contribute to the development of news portals to reduce cognitive overload and user disorientation. Presentes Information Architecture elements and journalistic inverted pyramid concepts. The research is quantitative, the epistemological grounds to address the problem is the General Systems Theory. Regarding cognitive overload and user disorientation in news portals chosen for analysis, it was observed that the environment A1 showed higher percentages for user satisfaction while using it, according to research data. It concludes that Information Architecture elements, present in news portals, help reduce cognitive overload, avoid confusion and maximize user satisfaction.
Arquitetura da informação em portais de notícias: Implicações relacionadas à sobrecarga cognitiva e à desorientação do usuário
Information architecture in news portals: Cognitive overhead and user disorientation implications
Keywords: Digital information environments; Hypertext; Information architecture; News portals; Webjournalism